2018
DOI: 10.1097/igc.0000000000001137
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of Adenomyosis in Myometrial Invasion and Overall Survival in Endometrial Cancer

Abstract: Our results showed that adenomyosis is significantly associated with lower stage in endometrial cancer that may suggest a possible limiting effect on endometrial cancer spread. In addition, despite similar rates in disease-free survival and endometrial cancer-related death, overall survival rate was significantly higher in the presence of adenomyosis and might be considered as a good prognostic factor for endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
(15 reference statements)
3
10
0
Order By: Relevance
“…This is in agreement with the current opinion that adenomyosis-associated endometrial cancer has a more favorable prognosis and might be a result of early diagnosis, due to the prominent symptoms of the two diseases (Habiba et al, 2018). On the other hand, the above-mentioned finding supports the idea, proposed by other authors (Koshiyama et al, 2004; Musa et al, 2012; Matsuo et al, 2014; Erkilinç et al, 2018), that adenomyosis can play a significant role as a prognostic factor in endometrial cancer, through its protective barrier effect to myometrial invasion of the tumor. Furthermore, our study included all histological subtypes, increasing the accuracy of our results, which was also suggested by Erkilinc S. et al (2018).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is in agreement with the current opinion that adenomyosis-associated endometrial cancer has a more favorable prognosis and might be a result of early diagnosis, due to the prominent symptoms of the two diseases (Habiba et al, 2018). On the other hand, the above-mentioned finding supports the idea, proposed by other authors (Koshiyama et al, 2004; Musa et al, 2012; Matsuo et al, 2014; Erkilinç et al, 2018), that adenomyosis can play a significant role as a prognostic factor in endometrial cancer, through its protective barrier effect to myometrial invasion of the tumor. Furthermore, our study included all histological subtypes, increasing the accuracy of our results, which was also suggested by Erkilinc S. et al (2018).…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, the above-mentioned finding supports the idea, proposed by other authors (Koshiyama et al, 2004; Musa et al, 2012; Matsuo et al, 2014; Erkilinç et al, 2018), that adenomyosis can play a significant role as a prognostic factor in endometrial cancer, through its protective barrier effect to myometrial invasion of the tumor. Furthermore, our study included all histological subtypes, increasing the accuracy of our results, which was also suggested by Erkilinc S. et al (2018). However, these results remain controversial, because other authors found adenomyosis as a risk factor for myometrial invasion and hence for worse prognosis ( Ismiil et al, 2007; Taneichi et al, 2014; Aydin et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We excluded 1501 studies after duplicates removal, 883 after title screening, and 14 after abstracts screening. Finally, 8 studies remained after whole study assessment [ 11 , 12 , 20 , 21 , 22 , 23 , 24 , 25 ]. The study by Erkilinc et al was excluded from the quantitative analysis because they randomly selected patients based on International Federation of Gynecology and Obstetrics (FIGO) grade of EC [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly used classification system in EC patients is the International Federation of Gynecology and Obstetrics (FIGO) staging system, in which patients with non-metastatic cancer are stratified based on the depth of myometrial invasion, cervical stromal invasion, as well as the extent of lymph node involvement (3). However, survival of patients with the same clinical stage varies widely because this system considers the survival rate independently from other prognostic factors such as age, tumor grade, and histologic type (4,5).…”
Section: Introductionmentioning
confidence: 99%